To solve this, you need to plug in the numbers for <em>h</em>.
-4(-12) ≥ 8 48 ≥ 8 yes
-4(-7) ≥ 8 28 ≥ 8 yes
-4(-5) ≥ 8 20 ≥ 8 yes
-4(-3) ≥ 8 12 ≥ 8 yes
-4(-2) ≥ 8 8 ≥ 8 yes
-4(-1) ≥ 8 4 ≥ 8 no
-4(1) ≥ 8 -4 ≥ 8 no
-4(3) ≥ 8 -12 ≥ 8 no
-4(8) ≥ 8 -32 ≥ 8 no
Hope this helped!
44
The pattern is +1,+1,x2
40° + 7 = 47
180° - 47 = 133°
Hope this Helps!!
Answer:
Part 1)
![m=170\°](https://tex.z-dn.net/?f=m%3D170%5C%C2%B0)
Part 2)
![x=-5, x=1](https://tex.z-dn.net/?f=x%3D-5%2C%20x%3D1)
![m=-10, m=14](https://tex.z-dn.net/?f=m%3D-10%2C%20m%3D14)
Step-by-step explanation:
we know that
In a parallelogram opposite sides and opposite angles are congruent, and consecutive angles are supplementary
Part 1)
<u>Find the value of x</u>
----> opposite sides are congruent
solve for x
<u>Find the value of m</u>
----> consecutive angles are supplementary
solve for m
![m=180\°-10\°=170\°](https://tex.z-dn.net/?f=m%3D180%5C%C2%B0-10%5C%C2%B0%3D170%5C%C2%B0)
Part 2)
<u>Find the value of x</u>
---> opposite sides are congruent
using a graphing tool
see the attached figure N 1
The solutions are
![x=-5, x=1](https://tex.z-dn.net/?f=x%3D-5%2C%20x%3D1)
<u>Find the value of m</u>
---> opposite sides are congruent
solve for m
using a graphing tool
see the attached figure N 2
The solutions are
![m=-10, m=14](https://tex.z-dn.net/?f=m%3D-10%2C%20m%3D14)
Answer:
The second term of the sequence is 8 False ⇒ B
The third term of the sequence is 3 True ⇒ A
The fourth term of the sequence is -3 True ⇒ A
Step-by-step explanation:
The form of the recursive rule is:
f(1) = first term; f(n) = f(n - 1) + d, where
- f(n - 1) is the term before the nth term
- d is the common difference
∵ f(1) = 15, f(n) = f(n - 1) - 6 for n ≥ 2
∴ The first term = 15
∴ d = -6
let us find the 2nd, 3rd, and 4th terms
∵ n = 2
∴ f(2) = f(1) - 6
∵ f(1) = 15
∴ f(2) = 15 - 6 = 9
∴ The second term is 9
∴ The second term of the sequence is 8 False
∵ n = 3
∴ f(3) = f(2) - 6
∵ f(2) = 9
∴ f(3) = 9 - 6 = 3
∴ The third term is 3
∴ The third term of the sequence is 3 True
∵ n = 4
∴ f(4) = f(3) - 6
∵ f(3) = 3
∴ f(4) = 3 - 6 = -3
∴ The fourth term is -3
∴ The fourth term of the sequence is -3 True